Cuentas por cobrar de la Cooperativa de Transporte en Taxis 9 de abril de la ciudad de Guayaquil en el período 2022-2023. - Guerrero Barragán, Jahanny Mariam (2024)
This investigative case study, it is focused on the Accounts Receivable of the 9 de Abril Taxi Transportation Cooperative of the City of Guayaquil in the Period 2022-2023. Where an internal control of accounts receivable was carried out to be able to identify in a more secure way what deficiencies have occurred within the organization, making its liquidity levels a low percentage, for those two types of control were applied. indicators that were the acid test and current liquidity, to obtain more information about this cooperative, the internal control questionnaire was also carried out to the manager, Mr. Víctor Gortaire Arguello. Therefore, this research presents as its primary objective the evaluation of accounts receivable, within which we use the analytical-descriptive variables for the interpretation of the information within the cooperative, providing a better perspective of its economy presented in financial statements. Finally, thanks to the information obtained in this case study, it could help to improve its liquidity deficiency situation and carry out better internal control within the entity.